Habitat fragmentation and food security in crop pollination systems. (12th July 2021) - Montoya, Daniel; Haegeman, Bart; Gaba, Sabrina; De Mazancourt, Claire; Loreau, Michel
Abstract: Ensuring stable food supplies is a major challenge for the 21st century. There is consensus that increased food production is necessary, but not sufficient, to achieve food security, and that agriculture should also aim at stabilizing crop production over time. In this context, biodiversity‐based approaches to food security are increasingly being supported based on the fact that biodiversity can increase and stabilize crop production. However, agricultural systems are often highly fragmented and our current understanding of how such fragmentation affects biodiversity and food production remains incomplete, thus limiting our capacity to manage agricultural landscapes for food security. We developed a spatially explicit model of crop dynamics to investigate how the fragmentation of natural habitats for agricultural conversion impacts food production and food security, with a focus on animal‐dependent crop production. Fragmentation produces a variety of spatial and biodiversity‐mediated effects that affect both the mean and stability (temporal invariability) of animal‐dependent crop production. Fragmentation has a dual effect on animal‐dependent production. On the one hand, spatial aggregation of natural land decreases animal‐dependent production by reducing the Landscape Pollination Potential, a metric that captures fragmentation and pollinator spillover effects within the agricultural landscape. But aggregation increases animal‐dependent production by maintaining a higher pollinator diversity in larger fragments of natural habitat. The net effects of fragmentation on animal‐dependent crop production depend on the land‐use change pattern, the strength of the pollinator spillover to crop land and the animal pollination dependence of crops. Synthesis . Our study sheds new light in the food security debate by showing that high and stable crop production depends on biodiversity and the spatial fragmentation of agricultural landscapes, and by revealing the ecological mechanisms of food security in crop pollination systems. Management for food security should consider factors such as pollinators' spillover, the amount and spatial aggregation of semi‐natural habitat and the animal pollination dependence of crops. This information would be useful to design agricultural landscapes for high Landscape Pollination Potential . These results are highly relevant in the global change context, and given the worldwide trends in agriculture, which shifts towards more animal‐dependent crop production. Abstract : Ensuring stable food supplies is a major challenge for the 21st century. This study shows that high and stable crop production depends on biodiversity and the fragmentation of agricultural landscapes, and reveals key ecological mechanisms of food security. These results are highly relevant in the global change context, and given the worldwide shifts in agriculture towards more animal‐dependent crop production. Resumen: Garantizar un suministro estable de alimentos es un desafío importante para el siglo XXI. Existe consenso de que el aumento de la producción de alimentos es necesario, pero no suficiente, para lograr la seguridad alimentaria, y que la agricultura debe estabilizar la producción de cultivos a largo plazo. En este contexto, los enfoques basados en la diversidad biológica reciben cada vez más apoyo sobre la base de que la biodiversidad puede aumentar y estabilizar la producción de cultivos. Sin embargo, los sistemas agrícolas a menudo están muy fragmentados y nuestra comprensión de cómo esa fragmentación afecta a la biodiversidad y a la producción de alimentos sigue siendo incompleta, lo que limita nuestra capacidad para gestionar paisajes agrícolas para la seguridad alimentaria. Desarrollamos un modelo espacialmente explícito de dinámica de cultivos para investigar cómo la fragmentación de hábitats naturales para la conversión agrícola impacta la producción de alimentos y la seguridad alimentaria, con un enfoque en la producción de cultivos dependientes de animales. La fragmentación produce una variedad de efectos espaciales y mediados por la biodiversidad que afectan tanto a la media como a la estabilidad (invariabilidad temporal) de la producción de cultivos dependientes de los animales. La fragmentación tiene un doble efecto sobre la producción dependiente de los animales. Por un lado, la agregación espacial del hábitat natural disminuye la producción dependiente de los animales al reducir el Potencial de Polinización del Paisaje, una métrica que captura la fragmentación y los efectos de propagación o ' spillover ' de los polinizadores dentro del paisaje agrícola. Sin embargo, la agregación aumenta la producción dependiente de los animales al mantener una mayor diversidad de polinizadores en fragmentos más grandes de hábitat natural. Los efectos netos de la fragmentación en la producción de cultivos dependientes de los animales dependen del patrón de cambio de uso del suelo, la fuerza de la propagación de los polinizadores a las tierras de cultivo y la dependencia de los cultivos de la polinización animal. Síntesis . Nuestro estudio arroja nueva luz en el debate sobre la seguridad alimentaria al mostrar que una producción de cultivos alta y estable depende de la biodiversidad y la fragmentación espacial de los paisajes agrícolas, y al revelar los mecanismos ecológicos de la seguridad alimentaria en los cultivos de polinización animal. La gestión para la seguridad alimentaria debe considerar factores como la propagación de los polinizadores, la cantidad y la agregación espacial del hábitat seminatural y la dependencia animal de los cultivos. Esta información sería útil para diseñar paisajes agrícolas con un alto Potencial de Polinización del Paisaje . Estos resultados son muy relevantes en el contexto del cambio global y dada la tendencia mundial de la agricultura, que se desplaza hacia una producción agrícola más dependiente de los animales.